Government standard operating procedures 2001 a basic handbook. - Fellowship of Christians in Government (Philippines). (Quezon City Fellowship of Christians in Government, 2001)
Contains basic steps in obtaining legal document from several government institutions in the Philippines. Most useful for Filipino citizens especially residents of Quezon City.
Keywords: Administrative agencies -- Philippines -- Handbooks, manuals, etc; Administrative agencies -- Philippines -- Rules and practice